The presence and the place of black teachers at IFMT: affirmative actions, advances and challenges (Research, Society and Development, 2021)
This article is the result of the research Project “Education and affirmative action: a study on the presence and place of black teachers at IFMT” developed at the Federal Institute of Education, Science and Technology of Mato Grosso. It aims to analyze, from a quantitative research the presence and place of black teachers in the IFMT educational and administrative structure. We specifically problematize this institution, in order to understand its locus in the scenario of implementation of affirmative action policies in Brazil after Durban (2001), considering that in the general context of public and private Brazilian universities it`s visible the small presence of black men and women professors in the didact and administrative structure of these academies. Therefore, the research assumes that the core of this problem is academic racism, justified by the myth of racial democracy, present in the work of Gilberto Freyre (2003). On the other hand, we deconstructed the idea of racial democracy, the main impediment to discussion of affirmative action policies in Brazil until 2001, the year of the Third Conference of Durban, having as theoretical support Florestan Fernandes (1972), Kabengele Munanga (1999, 2014), José Jorge de Carvalho (2003, 2006) and Nilma Lino Gomes (2005). It results from the investigation that combating racial inequality in higher education and university administrative instances requires new affirmative action measures that promote racial equality and, therefore, expand the presence and prominence of black professors in the academic environment.